2020
DOI: 10.1111/tmi.13397
|View full text |Cite
|
Sign up to set email alerts
|

Association of TP53 rs1042522 with cervical cancer in the sub‐Saharan African population: a meta‐analysis

Abstract: objective TP53 plays a crucial role in preventing cancer development. Previous studies in sub-Saharan Africa (SSA) reported inconclusive findings for the association of the TP53 rs1042522 C > G variant with cervical cancer. We therefore performed a meta-analysis to summarise this association in the SSA population.methods Online databases were searched to identify suitable articles according to the PRISMA guidelines. We included studies published in English or French that provided the sample sizes and genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…, 2019 ; Pouladi et al , 2019 ; Elshazli et al. , 2020 ; Kamiza et al, 2020 ; Liu et al , 2020 ) CTG (15.0%) 1 28.29 0.258 0.93-1.0 ACG (14.6%) -0.97 25.27 0.258 0.89-1.0 ATG (11.0%) -0.95 72.4 0.606 0.9-0.98 HNF1B CGG (49.3%) rs7501939 rs11651052 rs11658063 -0.95 72.4 0.606 0.9-0.98 rs7501939 ( Setiawan et al , 2012 ; Chornokur, 2013a ; Nikolić et al, 2014 ; Kristiansen et al. , 2015 ; Ríos-Tamayo et al , 2016 ; Oh et al, 2017a ; Tong et al., 2018 ) rs11651052 ( Painter et al , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019 ; Pouladi et al , 2019 ; Elshazli et al. , 2020 ; Kamiza et al, 2020 ; Liu et al , 2020 ) CTG (15.0%) 1 28.29 0.258 0.93-1.0 ACG (14.6%) -0.97 25.27 0.258 0.89-1.0 ATG (11.0%) -0.95 72.4 0.606 0.9-0.98 HNF1B CGG (49.3%) rs7501939 rs11651052 rs11658063 -0.95 72.4 0.606 0.9-0.98 rs7501939 ( Setiawan et al , 2012 ; Chornokur, 2013a ; Nikolić et al, 2014 ; Kristiansen et al. , 2015 ; Ríos-Tamayo et al , 2016 ; Oh et al, 2017a ; Tong et al., 2018 ) rs11651052 ( Painter et al , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study was based on 35 SNPs that can potentially modify the risk of cancer. A literature research revealed that only 10 of these 35 SNPs were described in studies of African or Afro-American populations ( Mechanic et al, 2007 ; Chornokur et al., 2013b ; Nikolić et al, 2014 ; Oh et al, 2017b ; Oussalah et al, 2017 ; Tong et al., 2018 ; Jones et al, 2019 ; Sagna et al, 2019 ; Song et al, 2019 ; Kamiza et al., 2020 ), suggesting that most association studies including these SNPs focused on European and Asian populations. The present results showed that a high number of individuals were homozygous for risk alleles with Native American and African ancestry that may modify the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our study set the OR value of the correlation between MDM2 rs2279744 polymorphism and cervical cancer as the reciprocal of 1.5 (i.e., 0.67). A review of the past literature indicated that the OR of the association between TP53 rs1042522 polymorphism and cervical cancer was 1.3 in the allele model (31). Consequently, the OR value of TP53 rs1042522 polymorphism and cervical cancer was set at 1.3.…”
Section: Trial Sequential Analysismentioning
confidence: 99%
“…Aberrant expression and dysfunction of TP53 have been detected in various human tumor cases. The TP53 rs1042522 C>G polymorphism leads to an amino acid alteration (Arg to Pro) and therefore influences the susceptibility of various malignant tumors (101)(102)(103). Our research group conducted two studies to explore the association between TP53 rs1042522 C>G polymorphism and hepatoblastoma.…”
Section: Other Genesmentioning
confidence: 99%